Eliminating fluoride-induced corrosion of aluminum cathodes in zinc electrowinning by aluminum ion complexation - N.G.S. Almeida; B.M. Ward; J.R. De Wet; A.D. Souza; V.S.T. Ciminelli; D. Majuste (Journal of Materials Research and Technology)
This paper discusses the effect of fluoride on the corrosion behavior of aluminum alloy used as a mother blank in zinc electrowinning, focusing on the mitigation of the corrosive process by aluminum ion addition and fluoride complexation. Standardized corrosion immersion tests have shown that increasing fluoride ion concentrations result in an increase in the corrosion rate of the aluminum alloy, but the addition of aluminum ions to the zinc sulfate electrolyte counteracts this effect by forming stable AlF2+ species. This favorable complexation reaction, thermodynamically modeled in this work, plays a critical role in reducing the activity of the corrosive HF species on the passive oxide layer of the aluminum surface. Electrochemical impedance spectroscopy and linear sweep voltammetry measurements supported these results. The presence of aluminum ions in the electrolyte, in amounts dependent on fluoride and sulfate concentrations, increases the charge transfer resistance at the interface and decreases the corrosion current. The work also proposes a method for the estimation of the amount of aluminum that is required to be added to the electrolyte in order to eliminate the fluoride-induced corrosion. The results of this research may help extend the life of the aluminum cathodes and thus reduce operating costs.